Determining The Optimal Amount of Bread Production with The Newsboy Problem Method at Adara Bakery and Cake - Fattahillah Rahmanda Harahap; Cut Ita Erliana; Muhammad Zakaria (Jurnal Informasi dan Teknologi, 2025)
Adara Bakery and Cake is one of micro small and medium enterprises that focus on bread production. The problem faced by Adara Bakery and Cake is an excess of products due to a production system that uses a continuous process method, which means that bread is produced continuously without considering the products sold. The objective of this study is to determine the optimal production quantity for the 8 most popular types of bread to be produced by Adara Bakery and Cake, as well as to identify the expected profits when production is at the optimal level. This study discusses the optimal production of the 8 most popular types of bread, namely chocolate brownies, pineapple roll cake, chocolate-topped bread, chocolate banana, black forest cake, slice cake, peanut pie, and dessert, using the newsboy problem method. Based on the research results, the optimal production quantity for chocolate brownies is 141 boxes, for pineapple roll cake is 191 boxes, for chocolate bread is 351 packages, for chocolate banana bread is 335 packages, for Black Forest cake is 237 boxes, for slice cake is 239 pieces, for peanut pie is 1, 779 pieces, and for desserts is 159 pieces. The expected profit for chocolate brownies is Rp 1,252,000, for pineapple roll cake is Rp 1,494,900, chocolate bread is Rp 595, 800, chocolate banana is Rp 532,000, Black Forest cake is Rp 3,890,000, sliced cake is Rp 535,500, peanut pie is Rp 2,538,200, and dessert is Rp 1,141,000.